Contemporary outcomes of bladder carcinoma in situ treated with an adequate bacille Calmette–Guérin immunotherapy. (23rd August 2021) - Subiela, José Daniel; Rodríguez Faba, Óscar; Aumatell, Júlia; Calderón, Julio; Mercadé, Asier; Balañà, Josep; Esquinas, Cristina; Algaba, Ferran; Breda, Alberto; Palou, Joan
Abstract : Objective: To assess whether bacillus Calmette–Guérin (BCG) responsiveness after initiation of an adequate BCG treatment (at least five of six instillations of induction and at least two of three instillations of maintenance) impacts oncological outcomes in patients with carcinoma in situ (CIS) of the bladder treated with BCG immunotherapy. Patients and Methods: Data were available for 193 patients with bladder CIS with or without associated cTa/cT1 disease who received an adequate BCG treatment between 2008 and 2015. Bladder biopsies were taken at 6 months and patients were then stratified as either BCG responsive (negative biopsies) or BCG unresponsive (positive biopsies). Inverse probability weighting (IPW)‐adjusted Kaplan–Meier and IPW‐adjusted Cox regression were performed to compare progression‐free survival (PFS), radical cystectomy‐free survival (RCFS), overall survival OS, and cancer‐specific survival (CSS) in the two groups. Results and Limitations: Comparing the BCG‐responsive and BCG‐unresponsive groups, IPW‐adjusted Kaplan–Meier analysis revealed, respectively, a median (interquartile range) of PFS of 9 (5–15) vs 48.5 (28–77) months ( P  = 0.001), a RCFS of 11 (9–15) vs 49 (24–76) months ( P  < 0.001), and a CSS of 25 (13–60) vs 109 (78–307) months ( P  = 0.004). On IPW‐adjusted Cox regression analysis, BCG‐unresponsive patients had a worse PFS (hazard ratio [HR] 3.40, 95% confidence interval [CI] 1.59–7.27), RCFS (HR 3.52, 95% CI 1.77–7), and CSS (HR 4.42, 95% CI 1.95–10.01). We found no significant differences for OS. Conclusion: Using an IPW method we found that lack of response after initiation of an adequate BCG treatment has prognostic implications beyond identification of complete response in patients with CIS. BCG‐unresponsive patients, satisfying the novel definition of BCG unresponsive, showed a poor PFS, RCFS, and CSS. In this setting, the patients should be counselled regarding RC as a first option or enrolled in a clinical trial if they refuse RC or are unfit for surgery.